IMPLEMENTATION OF MURABAHAH CONTRACT IN INDONESIA: A NARRATIVE STUDY OF THE PROCESS, CHALLENGES, AND ECONOMIC IMPACT - Kiki Afriani Putri; Fitri Wulandari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Murabahah is the most widely used sales-based financing instrument in Indonesian Islamic banking. This study aims to analyze the implementation of murabahah contracts in Indonesia based on the guidelines of the National Sharia Council-Indonesian Ulema Council (DSN-MUI), identify practical challenges in its implementation, and examine the economic impact on both banks and customers. This narrative study uses a systematic literature review approach with an analysis of 20 selected scientific journals from 1,000 identified documents. The findings of the study show that the implementation of murabahah contracts in Indonesia faces a significant gap between the provisions of the DSN-MUI fatwa and practices in the field, especially regarding the transfer of asset ownership, the use of wakalah (agency/authorization), and the choice of murabahah over alternative contracts. The economic impact is ambiguous: murabahah increases the bank's profitability but can reduce customer confidence if it is not in line with sharia principles. The findings of this study open up opportunities for the development of an innovative trade-based murabahah model to improve alignment with maqasid al-sharia and the resilience of Islamic banking. Keywords: Murabahah contract, sharia banking, DSN-MUI, sharia fatwa, wakalah